Investigation of the Electron Density Variation During the 21 August 2017 Solar Eclipse. Issue 3 (12th February 2018) - Reinisch, B. W.; Dandenault, P. B.; Galkin, I. A.; Hamel, R.; Richards, P. G.
Abstract: This paper presents a comparison of modeled and measured electron densities for the 21 August 2017 solar eclipse across the USA. The location of the instrument was (43.81°N, 247.32°E) where the maximum obscuration of 99.6% occurred at 17.53 hr UT on 21 August. The solar apparent time was 9.96 hr, and the duration of the eclipse was 2.7 hr. It was found that if it is assumed that there are no chromosphere emissions at totality, 30% coronal emission remaining at totality gave the best fit to the electron density variation at 150 km. The 30% coronal emission estimate has uncertainties associated with respect to uncertainties in the solar spectrum, the measured electron density, and the amount of chromosphere emissions remaining at totality. The agreement between the modeled and measured electron densities is excellent at 150 km with the assumed 30% coronal emission at totality. At other altitudes, the agreement is very good, but the altitude profile would be improved if the model peak electron density ( N m F 2 ) decayed more slowly to better match the data. The minimum N m F 2 in the model occurs 10 min after totality when it decreases to 0.55 from its noneclipse value. The minimum of the N m F 2 data occurs between 6 and 10 min after totality but is 15% larger. The total electron content decreases to 0.65 of its preeclipse value. These relative changes agree well with those predicted by others prior to the eclipse. Key Points: The h m F 2 rises from 220 to 260 km The N m F 2 falls to 55% of its noneclipse value The N m F 1 falls to 28% of its noneclipse value